The Moderating Influence of The Academic Supervision of Teacher Competencies and Commitment Towards Organizational of Teacher Performance - Irawan, Dony; Wahyudin, Agus; Yanto, Heri (Educational Management, 2018)
This research aims to know the influence of organizational commitment and competencies on performance teacher moderated academic supervision. While the issues rise in this study are: (1) tested the influence of organizational commitment, competence and supervision of academic performance against teachers, (2) to test whether moderate academic supervision competence and organizational commitment on performance of teachers. This research using a sample of high school teacher of Kesatrian Education Foundation under 67 Semarang as many as 101 teachers. Sampling by using census technique while model analysis using multiple regression analysis. The results obtained in this study are: (1) Competence proven positive and significant effect on performance of teachers, (2) significant Organizational Commitment has no effect on performance of teachers, (3) Academic Supervision proved to be moderate the relationship between Competences with the performance of teachers, (4) Academic Supervision unproven moderate the relationship between organizational commitments to the performance of teachers.